2008
DOI: 10.1093/molbev/msm271
|View full text |Cite
|
Sign up to set email alerts
|

Geological Dates and Molecular Rates: Fish DNA Sheds Light on Time Dependency

Abstract: Knowledge of DNA evolution is central to our understanding of biological history, but how fast does DNA change? Previously, pedigree and ancient DNA studies--focusing on evolution in the short term--have yielded molecular rate estimates substantially faster than those based on deeper phylogenies. It has recently been suggested that short-term, elevated molecular rates decay exponentially over 1-2 Myr to long-term, phylogenetic rates, termed "time dependency of molecular rates." This transition has potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
198
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(214 citation statements)
references
References 68 publications
(100 reference statements)
13
198
3
Order By: Relevance
“…However, because pervasive purifying selection is widespread among taxa, it is expected that similar selective processes would have occurred on a comparable timescale in the evolution of the taxa on which we based our clock rate priors (Meiklejohn et al, 2007;Burridge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because pervasive purifying selection is widespread among taxa, it is expected that similar selective processes would have occurred on a comparable timescale in the evolution of the taxa on which we based our clock rate priors (Meiklejohn et al, 2007;Burridge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Because inclusion of codons under positive selection may bias divergence estimates, we also removed putatively selected codons from the analysed dataset. Clock rates were chosen to encompass a range of mitochondrial time-dependent rates for comparably recent (o3 million years) divergences of galaxiids and other fishes, calibrated on the basis of geologically dated changes in river drainages and isolation events (0.003-0.13 substitutions/site/ million years; Burridge et al, 2008). To account for uncertainty in clock rates, we sampled clock rates from a distribution rather than setting fixed rates.…”
Section: Divergence Time Estimatesmentioning
confidence: 99%
“…Yet such discrepancies may indicate that rate heterogeneity and other features of the control region in humans rapidly generate homoplasy that complicates estimates of rates. Recent studies on time dependence of molecular rates indicate that substitution rates are generally underestimated in a phylogenetic comparison of old divergences, and that comparing more recently diverged taxa provides better estimates of instantaneous substitution rates (Ho et al 2005;Ho and Larson 2006;Burridge et al 2008). For whales, fossil dates for divergences are old because the fossil record of modern species is poor.…”
Section: Estimating Control Region Rate Using Cytochrome B Datamentioning
confidence: 99%
“…The latest example is the impressive study of fish mtDNA evolution (Burridge et al, 2008) where time-dependent rates are observed and , at least in part, due to the operation of purifying selection. However, pedigree rates do offer us an important insight to the early phase of selection (and other important evolutionary processes such as random genetic drift and bottlenecks) and this is why we must note here our disagreements with Dr Bandelt.…”
mentioning
confidence: 99%